(untitled) (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2025)
The article analyzes the role of Regulatory Standards (NRs 5, 6, 7, and 28) in enforcing workers’ fundamental rights to health, safety, and dignity, as provided for in the Federal Constitution and the CLT. It begins with a historical contextualization of labor protection, from the Industrial Revolution to the creation of the NRs by Ordinance No. 3,214/1978, which consolidated technical and legal parameters aimed at preventing accidents and occupational diseases. The research, which took a qualitative, descriptive, and deductive approach, was based on a bibliographic and documentary survey, with analysis of normative sources, doctrinal works, and testimonials from health and civil construction professionals, allowing for a connection between theory and practice regarding the application of the standards. The results show that NRs are essential instruments of labor protection: NR 5 (CIPA) encourages worker participation in safety management; NR 6 (PPE) ensures individual physical protection; NR 7 (PCMSO) promotes preventive health; and NR 28 ensures inspection and compliance with other standards. A significant reduction in occupational accidents and illnesses was observed, although challenges remain in terms of enforcement and awareness of the proper use of equipment and full compliance with legal guidelines. It is concluded that the NRs embody constitutional principles and strengthen human dignity in the workplace, transforming abstract rights into effective practices. Their effectiveness depends on joint action by the State, companies, and workers, based on education, prevention, and ethics. Thus, NRs not only fulfill a legal function, but also represent a social and civilizational commitment to valuing life and dignified work.